Pengelolaan Persediaan Bertingkat untuk Produk Perishable dengan Menerapkan Model Persediaan Multi-Echelon - Kholidasari, Inna; Aslam, Muhammad; Sundari, Susanti (Fakultas Teknik Universitas Tulang Bawang, 2026)
Inventory control is an important aspect in an organization or a company, especially a company which is deal with perishable products such as fruits An inventory model that considers the emission costs and the quality of products is Multi-Echelon Inventory Model. This research is a case study of a fruit shop where inventory control for high demand-value fruits is managed using the Multi-Echelon Inventory Model. This study aims to control the inventory of fruits in a fruit shop using Multi-Echelon Inventory Model. The data collection is carried out both in the cool room, where the fruits are consumed by the sales department, and in the sales area, where demand is generated by end consumers. Inventory costs were calculated for three fruit retrieval scenarios from the cool room, adjusted for fruit categories based on the time it takes for the fruit to deteriorate. Total inventory cost for scenario 1 is Rp.3.727.185,00, for scenario 2 is Rp. 3.698.675,00, and for scenario 3 is Rp 3.793.730,00. Total inventory cost are the combination between the inventory cost in the cool room and the inventory cost of sales area of sales department. The results f the research shows the total inventory cost to manage the products with high demand-value and also recommendations (scenario 3) on how to control the inventory system of fruit at the case organization. Keywords: Cool room, Inventory control, Multi-Echelon Model, Perishable Product